Analisis Pengaruh Harga Gabah, Impor, dan Produksi terhadap Kesejahteraan Petani : (Studi Kasus: NTP di Indonesia) - Felisia Wati Delta Fika; Muhamad Maulana; Ramadhan Agyat Wigunawan; Resha Moniyana Putri; Mega Mariska (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study examines the dilemma of rice import policy in Indonesia within the context of international trade and food security challenges. Rice, as a strategic commodity, holds significant social, economic, and political value, making import policies highly influential on price stability, farmers’ welfare, and national food security. The research identifies that import policies are often misaligned with domestic needs due to weak inter-institutional coordination, data inaccuracies, and pressures from political and business interests. As a result, import policies frequently create imbalances between the interests of consumers, traders, and local farmers, while also reducing the competitiveness of domestic rice due to inefficiencies in the distribution chain and post-harvest infrastructure. This study emphasizes the importance of data-based, transparent, and farmer-protective governance of rice import policies to strengthen national food security amid global trade liberalization pressures. hain, trade liberalization.